'Rew' (Immémorial #6): what is surfacing and submerging. Issue 1 (15th December 2012) - Weber, Pascale
Immémorial is a work in progress which was begun in 1996, written, conceived and created by Pascale Weber and which deals with memory and identity. Its six versions question the interactions between technology, science and creation. 'Rew' is the title of the sixth version. As an abbreviation of 'Rewind', it raises the spectre of travelling back in the past, of accessing our childhood secrets, of revisiting, maybe rewriting our identity. Immémorial #6: 'Rew' was shown in Marseille (Friche de la Belle de Mai) during the 2012 Music Festival, following a two-year residency at the Experimental Music Group of Marseille [GMEM], Euphonia and the Music and Informatics Laboratory of Marseille [MIM].The background and the lastest version of Immémorial allow us to investigate the relationship between technology, science and humanities. Science and the computer offer an emotional, aesthetical energy, a capacity to nourish poetry and imagination; the artist may intuitively propose free hypotheses, confronting his artistic project with scientific questioning, instead of giving meaning to his work. Doing so, he collaborates in the development of knowledge.Immémorial proposes a taxonomy of models of recollections which form our identity and deals with the dynamic functioning of our memory. Conversely, the structure of the computer language used for distributing the video image and sound spatialization guide the construction of the narrative and the return of the memorial experience in the device. Owing to the technical process of audio and visual spatialization, Immémorial projects the viewer into the heart of an environment, which is divided into 24 memorial moods based on poignant experiences, in order to awaken long-term memory.Immersive experiences pull us out of a reality too complex to grasp. This is the world narrowed in the heart of an enclosed space, a metaphor for a major societal issue: can we finally see the world as a plurality? Can we think outside of one's body, from other bodies, from a common body?